Traceless Liquid Phase Synthesis of Piperazinediones - Sun, C-M.; Swamy, K.M.; Lin, M-J.; Yeh, W-B.; Chen, F.Y.; Tseng, W-H. (Combinatorial Chemistry & High Throughput Screening, 2003)
Liquid phase combinatorial synthesis (LPCS) of piperazinediones by the use of soluble polymer support is explored to generate libraries. Proline anchored polyethylene glycol monomethyl ether (PEG) underwent dipeptide formation with different Fmoc-amino acids in the presence of dicyclohexyl carbodiimide (DCC). Deprotection of Fmoc accompanied with the cleavage from polymer support with cyclization of dipeptide to piperazinediones offers a facile and effective way to prepare diverse combinatorial libraries. Excellent yields and purities were achieved by simple wash and precipitation method.
Keywords: liquid phase combinatorial synthesis (lpcs)